(untitled) (Malaysian Journal of Learning and Instruction, 2023)
Purpose – The purpose of this study was to determine the relationship between trust, professional learning community, and self-efficacy. Methodology - This study used a quantitative approach via a survey that consisted of 47 items to collect relevant data. This survey included 112 primary schools with 642 Malaysian Islamic education teachers. A multilevel analysis was carried out to investigate the effect of group level variables (trust and professional learning community) towards the individual level variable (self-efficacy). Whereas, the mediator test used the Monte Carlo bootstrapping method. Findings - Findings of the study suggests that the professional learning community mediates the relationship between trust and self-efficacy. Significance - The results of this study showed that the professional learning community is the most important element in determining teacher self-efficacy. The outcomes of this study should also assist administrators in maintaining the professional learning community in schools so that it can work more efficiently and effectively. Keywords: Trust, Professional Learning Community, Self-Efficacy